The role of English in shaping the linguistic landscape in Slovenia - Šabec, Nada (ELOPE (Ljubljana), 2022)
The issue of visible written language used in Slovene public spaces is addressed. This is rapidly changing under the influence of English as the lingua franca of today. The names of stores, restaurants and other establishments as well as graffiti and other signs in Maribor, Slovenia’s second largest city, are examined. Four different locations are compared: the old city center, the city’s largest shopping mall, the Drava riverfront, and the student campus. Differences and similarities with regard to the ratio of different languages used are discussed in light of Slovenia’s language policy. They are also analysed from the linguistic perspective, focusing on lexical, syntactic and orthographic aspects. It is suggested that Slovenia should invest more effort both in the actual implementation of its language policy and language planning so as to guarantee that Slovene retains its status as official and state language not only de jure but also de facto.
Keywords: angleščina kot lingua franca; English as a lingua franca; jezikovna politika; language policy; Slovene linguistic landscape; slovenska jezikovna krajina